Double bundle arthroscopic Anterior Cruciate Ligament reconstruction with remnant preserving technique using a hamstring autograft - Ochi Mitsuo; Abouheif Mohamed M; Kongcharoensombat Wirat; Nakamae Atsuo; Adachi Nobuo; Deie Masataka (BMC, 2011)
Abstract Background Preservation of the Anterior Cruciate Ligament (ACL) remnant is important from the biological point of view as it enhances revascularization, and preserves the proprioceptive function of the graft construct. Additionally, it may have a useful biomechanical function. Double bundle ACL reconstruction has been shown to better replicate the native ACL anatomy and results in better restoration of the rotational stability than single bundle reconstruction. Methods We used the far anteromedial (FAM) portal for creation of the femoral tunnels, with a special technique for its preoperative localization using three dimensional (3D) CT. The central anteromedial (AM) portal was used to make a longitudinal slit in the ACL remnant to allow visualization of the tips of the guide pins during anatomical creation of the tibial tunnels within the native ACL tibial foot print. The use of curved hemostat allow retrieval of the wire loop from the apertures of the femoral tunnels through the longitudinal slit in the ACL remnant thereby, guarding against impingement of the reconstruction graft against the ACL remnant as well as the roof of the intercondylar notch. Conclusion Our technique allows for anatomical double bundle reconstruction of the ACL while maximally preserving the ACL remnant without the use of intra-operative image intensifier.